Meningkatan Kemampuan Berpikir Kritis Siswa Kelas X Melalui Model Pembelajaran Problem Based Learning di SMK Pertukangan Santo Yusup - Yonas Yonas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This Classroom Action Research (CAR) aims to improve the critical thinking skills of Grade X students at SMK Pertukangan Santo Yusup by applying the Problem-Based Learning (PBL) model. The background for this research is the previously low critical thinking skills of students, who tended to be passive and less actively involved in the learning process. The method used is Classroom Action Research (CAR) divided into two cycles, Cycle I and Cycle II, covering the stages of planning, implementation, observation, and reflection. In the first cycle, observation results showed that most students were still in the low category of critical thinking skills, with only a few reaching the "Proficient" category. After improvements in the second cycle, there was a significant increase. The number of students able to think critically in the "Proficient" category rose to 47%, and many students began to analyze, evaluate, and argue more effectively. The study also proved that the application of PBL increased students' active involvement in learning. They became more engaged in group discussions, problem-solving, and independent problem analysis. The classroom atmosphere also became more dynamic, with more positive interactions between students and between students and teachers. In conclusion, the PBL model is effective in improving students' critical thinking skills. The recommendations are to strengthen the implementation of PBL, develop relevant learning materials, provide sufficient time for learning, and conduct regular evaluations to ensure continuous improvement. With proper implementation, PBL can be further developed to help students hone their critical thinking skills.